Association between the expression of specific microRNAs and prostate cancer progression- a systematic review and meta-analysis - Alrehaili, Jihad Awadallah (Frontiers in Oncology, 2025)
BackgroundThis systematic review and metanalysis aimed to summarize the evidence supporting the significance of particular MiRNAs in PrCa progression and to thoroughly examine the body of prior research.MethodsIn accordance with the PRISMA guidelines, this review was conducted using a specifically design data extraction protocol and searching several online databases for relevant articles. The protocol was registered in the PROSPERO database (CRD42023428460).Results8 studies were ultimately included in this review. MiRNAs significantly reduced PrCa proliferation, with an odds ratio (OR) of 0.28 (95% CI: 0.21–0.39) and a risk ratio (RR) of 0.51 (95% CI: 0.43–0.61), though moderate heterogeneity was observed (I² = 57%). For two studies investigating MiRNAs as biomarkers for predicting metastasis, the pooled OR was 0.60 (95% CI: 0.47–0.76) and the RR was 0.72 (95% CI: 0.62–0.84), both demonstrating significant predictive value with low heterogeneity (I² = 0%).ConclusionThe results emphasize the potential of miRNAs as biomarkers for predicting PrCa metastasis and demonstrate that miRNAs have a discernible effect on PrCa proliferation. However, to improve our comprehension of MiRNA’s function in this condition, additional studies are required to address the limitations and investigate how MiRNA acts in many areas of PrCa.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023428460.